Peluang Jepang Untuk Menjadi Anggota Tetap Dewan Keamanan Pbb - Erna Kurniawati (Jurnal Paradigma, 2014)
Nowadays Japan has been known as one of the largest nancial contribution to the UN. Moreover, Japan has many times sent its military forces, Self Defence Forces (SDF) for some peace keeping mission under Peace Keeping Operation of the UN, either. In its situation, Japan feels it is really unfair, because Japan has done some important contribution and role for the existence of UN operation, but poorly, Japan is not a member of Security Council Permanent Member with its ‘veto’ privilege yet. So that, Japan asks members of the UN to do some reformation which it means that Japan will be have an chance to be a Security Council Permanent Member . This article will explore what has Japan been done to achieve its ‘dream’ and how its chance will be.